Pemanfaatan Limbah Batang Sawit dan Kotoran Kambing untuk Pembuatan Pupuk Kompos dengan Menggunakan Metode Dekomposer EM4 - Nina Veronika; Umar Linggom (Politeknik Kampar, 2024)
Oil palms have a lifespan of 25 -30 years, so at the end of the period, the oil palm trunks will be rejuvenated. In rejuvenation activities, the waste produced is around 220 m3 /ha. With the large amount of palm oil stem waste produced, it can be used as raw material for making compost fertilizer. The process of making compost fertilizer from palm oil stem waste is adapted to the process of making compost fertilizer in general. In this research, palm stem compost was also made using additional materials such as goat manure and rice bran. Parameters tested include C/N Ratio, C-Organic, NPK, and water content which were tested for 40 days.